Survival for patients with rare haematologic malignancies: Changes in the early 21st century. (October 2017) - ; Geiss, Karla; Meyer, Martin; Eberle, Andrea; Luttmann, Sabine; Stabenow, Roland; Hentschel, Stefan; Nennecke, Alice; Kieschke, Joachim; Sirri, Eunice; Holleczek, Bernd; Emrich, Katharina; et al.
Abstract: Introduction: Population-level survival has improved for common haematologic malignancies in the early 21st century. However, relatively few population-level data are available for rare haematologic malignancies. Methods: Data were extracted from 12 cancer registries in Germany and the Surveillance, Epidemiology and End Results database in the United States (US). Cases of haematologic malignancies with an incidence of less than 1 per 100, 000 were selected for analysis. Period analysis was used to determine 5-year relative survival (RS) for the years 2003–2012, and modelled period analysis was used to determine changes in survival between 2003–2007 and 2008–2012. Results: Seven individual haematologic malignancies which met criteria were identified. Overall 5-year age-adjusted RS was 62.4% in Germany and 57.0% in the US in 2003–2012, with a good deal of variability by individual haematologic malignancy, ranging from less than 30% for chronic monomyeloid leukaemia to greater than 85% for hairy cell leukaemia and mycosis fungoides. Five-year RS increased significantly between 2003–2007 and 2008–2012 for patients with mantle cell lymphoma, Burkitt's lymphoma and hairy cell leukaemia in Germany and for patients with mantle cell lymphoma and anaplastic large-cell kinase+ anaplastic lymphoma in the US. Conclusions: Survival for rare haematologic malignancies varied considerably by cancer entity. Overall 5-year RS was slightly higher in Germany compared to the US. Survival estimates increased for a minority of haematologic malignancies between 2003–2007 and 2008–2012. Further research into the best treatment options for rare malignancies is needed to further improve survival. Highlights: Survival for rare haematologic cancers has increased recently, but not to the degree as in more common haematologic cancers. Population-level survival for patients with rare haematologic malignancies was higher in Germany than in the United States. Survival and changes in survival for individual histologies varied considerably.